MODELING THE INTENSITY-MAGNITUDE-DISTANCE RELATION BASED ON THE CONCEPT OF AN INCOHERENT EXTENDED EARTHQUAKE SOURCE - Gusev A.A.; Shumilina L.S. (My University, 2000)
Parameters of short period motion radiated by earthquake sources were modeled to provide a theoretical description of macroseismic patterns. The energy contributions due to the radiating elements, source components that generate the field recorded by the receiver, were assumed to be additive. It is suggested that the integral of the square of accelerograms or the 'Arias intensity' can be used as a parameter suitable for predicting intensities (a modification of an approach developed by F.F. Aptikaev and N.V. Shebalin). The source of an earthquake is assigned a moment magnitude. Sources are assumed to obey geometrical similarity. The theory and empirical data are compared for two regions: Kamchatka-Kurils-Japan and continental North Eurasia. The far-field intensity vs. moment magnitude relation is practically linear and points to the growth of amplitude acceleration spectrum in accordance with the squared-omega-model or slightly faster. The method proposed here was employed to predict intensity in the two regions as a function of magnitude and distance using the extended source model.